PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 05 JAYAPURA - Harsono, Harsono; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is a classroom action research that aims to improve the learning mathematics outcomes in the third grade students of SD Negeri 05 Jayapura by applying the type of cooperative learning model Think Pair Share (TPS). The low yield is due to students' learning model used by teachers in teaching mathematics less varied, tends to dull the learning process so that students are less motivated to learn. This research was conducted in the second half (even) in the academic year 2014/2015. The subjects were students of class III SD Negeri 05 Jayapura, as many as 29 people, consisting of 17 men and 12 women. This thesis presents the results of student learning tests showed significant improvement with the implementation of cooperative learning Think Pair Share (TPS). This research is a form of classroom action research consisting of 2 cycles. Research instruments include learning device (syllabi, lesson plans, worksheets) as well as observation sheets teachers and students. The results showed that the learning outcomes and increases the activity of teachers and students. Student learning outcomes in the first cycle an average of 75.52 with 21 students completed the completeness percentage of 72.41% increased in the second cycle average of 81.03 at 27 students completed the completeness percentage of 93.10%. The activities of teachers in the first cycle are categorized as being increased in the second cycle were considered good. Activity of students in the first cycle of the first meeting were categorized fairly elevated in the second meeting acquire either category, then on the second cycle increased categorized as good. It can be concluded that the application of cooperative learning Think Pair Share (TPS) can improve mathematics learning outcomes third grade students of SD Negeri 05 Jayapura.Keywords: Cooperative Learning Model Type Model Think Pair Share (TPS), Mathematics Learning Outcomes